Analysis of Prognostis Factors and Effect of Pulmonary Rehabilitation in Patients with Chronic Obstructive Pulmonary Disease - Yiming XU; Honghua SHEN; Jingbo DU; Lei REN (康复学报)
Objective:To evaluate the rehabilitation effect of different intensity aerobic exercise on patients with chronic obstructive pulmonary disease (COPD), and explore an appropriate pulmonary rehabilitation strategy for COPD patients with different degrees of pulmonary function in alleviating period.Methods:A total of 529 COPD patients were from the respiratory department of Shanghai Fourth Rehabilitation Hospital. All patients were given the treatments: ①Routine medical treatment of COPD, included bronchodilator, hormones and β2receptor agonist (the patients whose FEV1 accounted for less than 50%of the predicted value and having clinical symptoms were treated with inhaled hormones and β2receptor agonist), and other expectorant and cough-relieving drugs.②Pulmonary rehabilitation education, included knowledge of COPD, pulmonary rehabilitation idea, smoking cessation, oxygen therapy, rational use of drugs and balanced nutrition, once a month.③Aerobic respiratory exercises, included lip contraction breathing and abdominal breathing training, 5 times a week, 20 minutes each time.④Aerobic exercise training, limited aerobic exercise with different intensity from low to high using randomized block design. All patients completed aerobic exercise of different intensity for 20 weeks, and postoperative life quality, treatment, and survival time of the patients were followed up for 2 years. The factors affecting survival were investigated, and Cox regression analysis was used to analyze various factors affecting the survival of COPD patients.Results:①The 38 cases of COPD grade III died of respiratory diseases, and 43 cases of COPD gradeⅣdied of respiratory diseases.②According to the single factor correlation analysis, pulmonary function grade, BODE index, aerobic exercise intensity and frequency of acute episodes were the factors influencing the survival rate of COPD patients within two years after 20-week pulmonary rehabilitation (P< 0.05), but sex, age, and the use of noninvasive ventilator had no obviously effect on survival rate of the COPD patients (P> 0.05). ③From multifactor correlation analysis, pulmonary function grade, BODE index, aerobic exercise intensity and frequency of acute episodes were the factors influencing the survival rate of COPD patients within two years after 20-week pulmonary rehabilitation (P< 0.05), but the use of noninvasive ventilator had no obviously effect on survival rate of the COPD patients (P> 0.05). Furthermore, pulmonary function grade, BODE index, and frequency of acute episodes were the risk factors affecting the prognosis of COPD patients, and aerobic exercise was the protective factor affecting the prognosis of COPD patients.④According to the survival curve of COPD patients, the survival curve of COPD patients undergoing high strength aerobic exercise intervention was higher than COPD patients undergoing middle strength aerobic exercise intervention, and the survival curve of COPD patients undergoing low strength aerobic exercise intervention was the least. On the contrary, the cumulative risk of COPD patients undergoing high strength aerobic exercise intervention was lower than COPD patients undergoing middle strength aerobic exercise intervention, and the cumulative risk of COPD patients undergoing low strength aerobic exercise intervention was the most.Conclusion:The worse the pulmonary function, the higher the BODE index, and the more times of acute exacerbations, the higher the mortality rate of COPD patients. In addition, aerobic exercise can improve the survival of COPD with chronic obstructive pulmonary disease within two years. What's more, the patients with high intensity aerobic exercise benefit the most.